ROMANSY 21 - Robot Design, Dynamics and Control Proceedings of the 21st CISM-IFToMM Symposium, June 20-23, Udine, Italy - Parenti-Castelli, Vincenzo; Schiehlen, Werner (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2016)
This proceedings volume contains papers that have been selected after review for oral presentation at ROMANSY 2016, the 21th CISM-IFToMM Symposium on Theory and Practice of Robots and Manipulators. These papers cover advances on several aspects of the wide field of Robotics as concerning Theory and Practice of Robots and Manipulators. ROMANSY 2016 is the 21st event in a series that started in 1973 as one of the first conference activities in the world on Robotics. The first event was held at CISM (International Centre for Mechanical Science) in Udine, Italy on 5-8 September 1973. It was also the first topic conference of IFToMM (International Federation for the Promotion of Mechanism and Machine Science) and it was directed not only to the IFToMM community.